PENERAPAN STRATEGI PEMBELAJARAN FIRE-UP UNTUK MENINGKATKAN PRESTASI BELAJAR SISWA PADA POKOK BAHASAN HIDROLISIS GARAM DI KELAS XI SMA BABUSSALAM PEKANBARU - Hasnul Habiba; Johni Azmi; Sri Haryati (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract:This research aims to increase student achievement on the subject Hydrolysis of Salt in class XI SMA BABUSSALAM PEKANBARU. This research is a kind of experiment research with pretest-posttest design. The research was conducted in SMA BABUSSALAM PEKANBARU. The samples of this research were the students of class Xl IPA 1 as the experimental class and students of class XI IPA 2 as the control class. Experimental class is a class that is applied active learning strategy FIRE-UP, while the control class was not. Data analysis technique used is the t-test. Based on analysis of data obtained tarithmetic> ttable is 3,78 > 1,67, means that the application of active learning strategy FIRE-UP can improve student achievement on the subject of Salt Hydrolysis in class XI Science SMAN BABUSSALAM PEKANBARU increase learning achievement category in the experimental class is based on the normalized gain scores (N-Gain) relatively high at 0.7138.Keywords : Learning Strategy FIRE-UP, Learning Achievement, and Hidrolysis of Salt